Toward sustainable transportation: a pavement strategy selection based on the extension of dual-hesitant fuzzy multicriteria decision-making methods - Alamoodi, Abdullah Hussein (Tanjung Malim, 2023)
Toward sustainable transportation: a pavement strategy selection based on the extension of dual-hesitant fuzzy multicriteria decision-making methods by Alamoodi, Abdullah Hussein